3(-6)+2y=6

Simple and best practice solution for 3(-6)+2y=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-6)+2y=6 equation:


3(-6)+2y=6

We simplify the equation to the form, which is simple to understand
3(-6)+2y=6

Reorder the terms in parentheses
+(-18)+2y=6

Remove unnecessary parentheses
-18+2y=+6

We move all terms containing y to the left and all other terms to the right.
+2y=+6+18

We simplify left and right side of the equation.
+2y=+24

We divide both sides of the equation by 2 to get y.
y=12

See similar equations:

| -6(x-2)+4(5n-3)=-36 | | 4(b+1)=-2(b+2) | | 8+x-1/x+4 | | -5-2(-6)=7 | | 49w^2-16w=0 | | 2x+3=-18+x | | 13b-6=3b+4 | | -2(-7k+5)+9=-13 | | 229-4x=32x+17 | | 1/9x^2+2/3x-3=0 | | 6-8x=114-29x | | x/5+x/7=8/7 | | 8(x+2)-2=22-4x-8+12x | | 5x+5=10x-20 | | 9x-5y=18 | | 12r^2=27+27r | | 2x+5=115-10x | | 12+2x=2-4x | | -4(t-1)+9t=8t-8 | | 6c^2+9c/3c | | -5(t-1)+7t=6t-6 | | n-14=16 | | 51-3x=10x+22 | | -5+6(x-3)=15x+3-9x | | -9(t+2)=54 | | 0.5x-0.3(10-3x)=-0.6(x-5) | | 13=13 | | 1/6x-3=5 | | -7/8v=35 | | 3+y/2=3y/4-2 | | x^2+10x+98=0 | | 6+6x=42+x |

Equations solver categories